Sexual inequality in incident tuberculosis: a cohort study in Taiwan. Issue 2 (6th February 2018) - Yen, Yung-Feng; Hu, Hsiao-Yun; Lee, Ya-Ling; Ku, Po-Wen; Ko, Ming-Chung; Chuang, Pei-Hung; Lai, Yun-ju; Chu, Dachen
Abstract : Objective: Animal studies showed that male subjects had lower activity of immune response to infections than female subjects, which may increase the risk of the development of tuberculosis in male population. This study intended to investigate the risk of incident tuberculosis in male and female adults in Taiwan. Design: This is a retrospective cohort study. Setting: The present analyses used data of Taiwan National Health Interview Survey 2001, 2005 and 2009, National Register of Deaths Dataset, and National Health Insurance Research Database from 2000 to 2013. Participants: A total of 43 424 subjects with a mean age of 43.04 years were analysed. Primary outcome measures: Incidence of tuberculosis. Results: During 381 561 person-years of follow-up period, incident tuberculosis was recognised in 268 individuals. The incidence rates of tuberculosis were 97.56 and 43.24 per 100 000 person-years among male and female participants, respectively. Kaplan-Meier curves comparing male and female subjects showed statistical significance (log-rank test, P value<0.01). After adjusting for subjects' demographics and comorbidities, men showed increased risks of incident tuberculosis (adjusted HR, 1.68; 95% CI 1.21 to 2.34; P value<0.01) compared with women. On subgroup analysis, after stratifying by age, smoking and alcohol use, men had a higher risk of incident tuberculosis than women in all patient subgroups, except those who were current smokers. Conclusions: This study suggests that men had a higher risk of incident tuberculosis than women. Future tuberculosis control programmes should particularly target the male population.